Virtual Keyboard Design of Lampung Script Based on Android - Bagaskara, Pratama Yuda; Muhammad, Meizano Ardhi; Mardiana, Mardiana; Komarudin, M (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Lampung script fonts, in general, can only be used for typing on a computer system and have not been developed for typing on Android-based smartphones. Therefore, efforts to modernize and build typing using Lampung script for smartphone needs are very much needed on mobile phones so they can be used flexibly. This research makes a virtual keyboard / android keyboard application that can do typing using Lampung script. The virtual keyboard layout is designed by adopting several layouts found on the QWERTY keyboard by displaying all Aksara letters on one virtual keyboard display and grouping Aksara letters in a more attractive composition. To test the Lampung virtual keyboard script, the researchers used the usability testing method, namely aspects of effectiveness, efficiency, and user satisfaction, by 25 respondents. Through this test, an assessment of the effectiveness of the typing test on the success rate of respondents in doing the task was obtained, which was 75 percent. Evaluation of the typing efficiency aspect using time calculation gets the average result on the WPM score analysis, which is 34 WPM. This result is still below the average typing speed of people, which is 38 WPM. Testing on the aspect of user satisfaction using the system usability scale (SUS) method gets a SUS value of 76, and this result is included in the Acceptable/Good category Acceptable/Good so that users can type Lampung script through Android phones. The conclusion is that it can produce an optimal, efficient virtual keyboard layout and provide comfort for the user while using it with Android. It also could introduce the Lampung script to the younger generation.